Public-Private Partnerships and Sustainable Development Goals in Nigeria - Obasa, Stephen Olufemi Obasa; Oluyomi, Oluwatosin Olatunji Oluyomi (African Journal of Stability and Development (AJSD), 2024)
The attempt by the United Nations (UN) to assist member states, especially developing countries with huge financing gaps, to meet the 17 sustainable development goals (SDGs) necessitated the need for public-private partnerships (PPPs) as a financing strategy. The PPP initiative is generated by the World Bank to give policy advice to developing economies on the need to involve the private sector in financing and operating infrastructure. The paradigm shift from traditional public service delivery to public-private partnerships (PPPs) is a modern financing strategy for mobilising resources so that developing countries characterised by constrained resources can optimise the public utilities, and more importantly, meet the SDGs targets by 2030. The study provides insights into the wide variety of PPP arrangements and the sometimes rather diffused contractual framework under which PPPs take place. Due attention is given to the motives and rationale for relying on PPPs and the expected outcomes of PPP arrangements. A major conclusion derived from this study is that, for sustainable development goals to be achieved in developing economies, the partnership should not be limited to resource sharing, but also involve accountability, people-centredness, risk-sharing and revenue distribution between the public and private stakeholders. The study adopts a qualitative research method, encompassing the use of journals, books, internet materials and secondary data.